Pemanfaatan Instagram Sebagai Media Komunikasi Pemasaran Pariwisata Malino di Kabupaten Gowa, Sulawesi Selatan - Yulia Permatasari; M. Iqbal Sultan; Muhammad Akbar; Andi Subhan Amir (Dialektika: Jurnal Ekonomi dan Ilmu Sosial)
The rapid competition in the digitalization era has brought many changes in the industrial sector, one of which is the tourism industry. This requires the tourism industry to continue to make various innovations, including innovating in the application of the right marketing strategy in order to be able to adapt and compete well. This research aims to analyze the digital marketing communication strategy used in promoting Malino tourist destinations through the use of Instagram. This research uses a qualitative descriptive method. Data collection techniques were carried out by means of in-depth interviews, observation, and documentation. The results showed that the utilization of Instagram as a marketing communication medium for Malino tourist destinations, using an endorsement system, sale promotion, brand building, competitor review, and consistent interaction with followers proved effective in increasing tourist visits to Malino.